2011
DOI: 10.1016/j.epsl.2010.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Chemical fractionation in the silicate vapor atmosphere of the Earth

Abstract: Despite its importance to questions of lunar origin, the chemical composition of the Moon is not precisely known. In recent years, however, the isotopic composition of lunar samples has been determined to high precision, and found to be indistinguishable from the terrestrial mantle, despite widespread isotopic heterogeneity in the Solar System. In the context of the giant impact hypothesis, a high level of isotopic homogeneity can be generated if the proto-lunar disk and post-impact Earth undergo turbulent mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 53 publications
0
76
1
Order By: Relevance
“…Recent theoretical studies show that too much silicate vapor would prevent the formation of moon after a giant impact [e.g., 3]. However, the presence of silicate vapor may help the equilibration of oxygen isotope [4] and the chemical fractionation of Mg# ,Mg/(Fe+Mg) [24], between the Earth and the Moon. Thus, there should be an intermediate successful range of the degree of vaporization for the giant impact hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent theoretical studies show that too much silicate vapor would prevent the formation of moon after a giant impact [e.g., 3]. However, the presence of silicate vapor may help the equilibration of oxygen isotope [4] and the chemical fractionation of Mg# ,Mg/(Fe+Mg) [24], between the Earth and the Moon. Thus, there should be an intermediate successful range of the degree of vaporization for the giant impact hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…This would argue for a source of fresh material, which would have had to be produced within the last 0.1 Myr to be consistent with SiO recondensation. Recently, Pahlevan et al (2011) showed that silicate constituents (Si, Fe, Mg and O) can be produced in the form of gas during hypervelocity collisions. Therefore, one can speculate that the origin of atomic oxygen detected with Herschel could be the violent event proposed by Lisse et al (2009) to explain the shape of the Spitzer/IRS spectrum.…”
Section: Recent Release During a Catastrophic Eventmentioning
confidence: 99%
“…The similarity in abundances of refractory elements implies that processes in the protolunar disc did not lead to relative fractionation of refractory elements or to a general enrichment during condensation and partial crystallization of the disc before the Moon accreted from it. Chemical models of disc processes [59][60][61] need to account for the approximate similarity with terrestrial abundances of refractory elements.…”
Section: Implications For Lunar Originmentioning
confidence: 99%